Identification of repetitive atrial activation patterns in persistent atrial fibrillation by direct contact high‐density electrogram mapping. (15th October 2019) - Wolf, Michael; Tavernier, René; Zeidan, Ziad; El Haddad, Milad; Vandekerckhove, Yves; Pooter, Jan De; Phlips, Thomas; Strisciuglio, Teresa; Almorad, Alexandre; Kyriakopoulou, Maria; Lycke, Michelle; Duytschaever, Mattias; et al.
Abstract: Introduction: Recent studies have characterized drivers in persistent atrial fibrillation using automated algorithm detection with panoramic endocardial mapping by means of basket catheters. We aimed to identify repetitive atrial activation patterns (RAAPs) during ongoing atrial fibrillation (AF) based upon automated annotation of unipolar electrograms (EGMs) recorded with a high‐density regional endocardial contact mapping catheter. Methods: In 14 persistent AF patients, high‐resolution EGMs were recorded for 30 seconds at sequential PentaRay (Biosense Inc) positions covering the entire biatrial surface. All recordings were reviewed off‐line with dedicated software allowing automated annotation of the local activation time of the unipolar fibrillatory EGMs (CARTOFINDER; Biosense Inc). RAAPs were defined as a consistent activation pattern (for ≥3 consecutive beats) of either focal activity with centrifugal spread (RAAPfocal ) or rotational activity across the PentaRay splines spanning the AF cycle length (RAAProtational ). Results: A total of 498 PentaRay recordings were analyzed (35.6 ± 7.6 per patient). The number of PentaRay recordings displaying RAAP was 9.8 ± 3.1 per patient (range = 3‐15), of which 2.4 ± 2.4 RAAProtational (range = 0‐7), and 7.4 ± 4.4 RAAPfocal (range = 1‐13). 77% of RAAPs portrayed focal firing. The median number of repetitions per 30 second recording was 11 (range = 3‐225) per recording. RAAPs were observed both in the right atrium (RA) (35%) and left atrium (LA) (65%), with the majority being near the left PVs/appendage (35% of all RAAPs) and the superior vena cava/right appendage (23% of all RAAPs). Conclusion: High‐resolution, sequential endocardial EGM‐based mapping allows identification of RAAPs in persistent AF. In our series, focal firing was the most frequently observed pattern.